Intersection of inflammation and viral replication: the central role of MAPK signaling in viral respiratory infections - Tripp, Ralph A.; Jones, Les P.; Martin, David E. (Frontiers in Microbiology, 2026)
The mitogen-activated protein kinase (MAPK) pathway is a vital cellular signaling cascade that viruses exploit. When activated by viruses, this pathway also initiates the host’s inflammatory response. This pathway has a crucial role in viral respiratory infections, serving as a key intersection where viral replication and host inflammation are coordinated. Some viruses activate this pathway to enhance their own replication while also triggering inflammatory responses in the host. Understanding this intersection is essential because therapeutic agents could target the same pathway to inhibit both viral replication and inflammation. This perspective considers targeting the MAPK pathway as a potential way to treat viral respiratory infections by suppressing viral replication and reducing inflammation.